JIZZAX VILOYATI FAUNASINING TURISTIK AHAMIYATI - Gʻoʻdalov, M.R.; Mirzayeva, A.Z. (SCIENCE and SOCIETY, 2025)
Jizzakh region is located in the central part of Uzbekistan, is distinguished by its natural beauty, historical monuments and cultural heritage. The importance of the fauna in the development of tourism in this region is of particular importance. The fauna not only enriches the natural environment, but also provides interesting and educational experiences for tourists. The fauna of Jizzakh region plays an important role in expanding its tourism opportunities. This article provides information on the touristic importance of the fauna in the development of tourism in Jizzakh region.